Systematic Review: Tantangan Pelayanan Pengobatan Pasien TB Saat Pandemi Covid-19 - Muflihah, Ahdiah Imroatul; Martha, Evi (Jurnal Kesehatan, 2022)
The Covid-19 pandemic is affecting global health issues. The interaction between Covid-19 patients and Tuberculosis makes it the number one cause of death worldwide. Numerous deaths caused by Covid-19 are reported every day in Indonesia, leading to a reduced number of TB patients who require routine treatment to health services in the community. Therefore, this review aimed to identify challenges in treatment services for TB patients during the Covid-19 pandemic. The study design used was a systematic review to identify the challenges in treatment services for TB patients during the Covid-19 pandemic. The challenges are a low-capacity health system, lack of knowledge about health, less-optimum treatment for TB patients due to social restrictions, limited regular visits to health services, and low TB case detection. To prevent negative impacts in reduced treatment for TB patients, telemedicine can be used, proper knowledge can be provided through social media, and consistent policies can be implemented to strengthen the weakening health system.